Børn og dyr i Danmarks kalkmalerier - Olsen, Rikke Agnete (Hikuin, 2007)
Children and Animals in Danish Wall Paintings By Rikke Agnete Olsen Children and animals in Danish medieval wall-paintings show how the range of themes in the paintings and certainly elsewhere also represented by children and animals is very wide. Accordingly the mental horizon in the period must have been wide also. The church would never paint anything that was not publicly understood. The church must have decided what to paint, as it could not have accepted anything crossing its content. Pictures obviously critical of the church must reflect the division of the church.